1988
DOI: 10.1055/s-2008-1043419
|View full text |Cite
|
Sign up to set email alerts
|

Time-Space Distribution of Extrahepatic Biliary Atresia in The Netherlands and West Germany

Abstract: Extrahepatic biliary atresia (EHBA) is an infrequent disease confined to early infancy. Its aetiology is not clear, but an infectious agent has been implicated. Demonstration of a time-space clustering would support this hypothesis. Therefore, we investigated the time-space distribution of all 89 cases of EHBA born in a 10-year period in the Netherlands. We carried out a similar study in West Germany and analysed 130 cases of EHBA, born between 1969 and 1986, from 4 paediatric surgical centres. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 3 publications
3
39
4
1
Order By: Relevance
“…Incidence of BA atresia in Croatia (1:23,600) is lower than incidence reported in other European studies (it varies between 1:14,000 and 1:20,000) but still belongs to the confidence interval of Swiss and Dutch studies [4,9,11,14,24]. It is reasonable to hypothesize that unfortunate circumstance in the first years of our survey which caused great migrations of people to Western countries must be taken in account when interpreting our data.…”
Section: Discussioncontrasting
confidence: 70%
“…Incidence of BA atresia in Croatia (1:23,600) is lower than incidence reported in other European studies (it varies between 1:14,000 and 1:20,000) but still belongs to the confidence interval of Swiss and Dutch studies [4,9,11,14,24]. It is reasonable to hypothesize that unfortunate circumstance in the first years of our survey which caused great migrations of people to Western countries must be taken in account when interpreting our data.…”
Section: Discussioncontrasting
confidence: 70%
“…The incidence of BA ranges from 0.5 per 10 000 live births in the Netherlands to 3.2 in French Polynesia [9,10], and in Japan, the incidence is 1.0 to 1.2 per 10 000 live births according to the registry data of Japanese Biliary Atresia Society [1]. The present population-based study of BA found an incidence of 1.1/10 000 live births in the Hyogo area.…”
Section: Discussionmentioning
confidence: 92%
“…The NS et al observed that conception during spring was more associated with the occurrence of BA than conception during winter 9 . Other groups from different countries have found no association of BA with seasonality 5,[10][11][12]19 . Different investigation methods, samples sizes, and environmental or weather conditions in different regions may explain these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the conception of a patient with BA was 84% less likely if this condition was diagnosed in winter, suggesting a seasonal influence on BA etiology, although season at birth was not associated with the occurrence of BA. Seasonality suggests that environmental factors can trigger BA, but conflicting results have been described on this topic [9][10][11][17][18][19] . In Texas, a higher number of BA patients were born during summer and spring in the countryside, suggesting that the noxious agent could be an agricultural toxin 17 .…”
mentioning
confidence: 99%